Long-range Stripe Nanodomains in Epitaxial (110) BiFeO3 Thin Films on (100) NdGaO3 Substrate - Yogesh Sharma (Nature Portfolio, 2017)
Abstract Here, we report the observation of ferroelectric and ferroelastic nanodomains in (110)-oriented BiFeO3 (BFO) thin films epitaxially grown on low symmetric (100) NdGaO3 (NGO) substrate. We observed long range ordering of ferroelectric 109° stripe nanodomains separated by periodic vertical domain walls in as-grown 130 nm thick BFO films. The effect of La0.67Sr0.33CoO3 (LSCO) conducting interlayer on domain configurations in BFO/NGO film was also observed with relatively short range-ordering of stripe domains due to the modified electrostatic boundary conditions in BFO/LSCO/NGO film. Additional studies on B-site doping of Nb ions in BFO films showed change in the domain structures due to doping induced change in lattice anisotropy while maintaining the stripe domain morphology with 109° domain wall. This long-range array of ferroelectric and ferroelastic domains can be useful for optoelectronic devices and ferroelastic templates for strain coupled artificial magnetoelectric heterostructures.